Prompt Engineering and Experiential Learning Design: Using artificial intelligence to help focus on the learning that matters. - Snyder, Martha (Experiential Learning and Teaching in Higher Education, 2025)
Prompt engineering is a method of crafting a set of instructions (or prompt) to input into a generative AI application (such as ChatGPT), to produce better output. These prompts can provide context and direction to a conversation by telling the application what to pay attention to and what the desired output should look like. In this paper, readers will learn what prompt engineering is and why it is relevant to experiential learning design. A simple prompt pattern is used to guide the phrasing of prompts for three examples: designing a debrief script for a simulation, creating reflection questions for a service-learning experience, and using generative AI as a learning partner/tutor. The goal is to ignite the imagination of the readers for how they might design their own prompts to be more efficient and effective in their experiential learning design efforts.